5(x-6)-6(x-5)=x+2-(x-3)

Simple and best practice solution for 5(x-6)-6(x-5)=x+2-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-6)-6(x-5)=x+2-(x-3) equation:


Simplifying
5(x + -6) + -6(x + -5) = x + 2 + -1(x + -3)

Reorder the terms:
5(-6 + x) + -6(x + -5) = x + 2 + -1(x + -3)
(-6 * 5 + x * 5) + -6(x + -5) = x + 2 + -1(x + -3)
(-30 + 5x) + -6(x + -5) = x + 2 + -1(x + -3)

Reorder the terms:
-30 + 5x + -6(-5 + x) = x + 2 + -1(x + -3)
-30 + 5x + (-5 * -6 + x * -6) = x + 2 + -1(x + -3)
-30 + 5x + (30 + -6x) = x + 2 + -1(x + -3)

Reorder the terms:
-30 + 30 + 5x + -6x = x + 2 + -1(x + -3)

Combine like terms: -30 + 30 = 0
0 + 5x + -6x = x + 2 + -1(x + -3)
5x + -6x = x + 2 + -1(x + -3)

Combine like terms: 5x + -6x = -1x
-1x = x + 2 + -1(x + -3)

Reorder the terms:
-1x = x + 2 + -1(-3 + x)
-1x = x + 2 + (-3 * -1 + x * -1)
-1x = x + 2 + (3 + -1x)

Reorder the terms:
-1x = 2 + 3 + x + -1x

Combine like terms: 2 + 3 = 5
-1x = 5 + x + -1x

Combine like terms: x + -1x = 0
-1x = 5 + 0
-1x = 5

Solving
-1x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-1'.
x = -5

Simplifying
x = -5

See similar equations:

| 12n-24=14n+28 | | x^3+x^2=25 | | 7(1-s)=-2(5s+4)+6s | | 3n+11=-16 | | 4y-9=18y+5 | | 2f-6=75+24 | | 10x+10=8x+2 | | 4(2-x)-3(7x+5)+6(3x-1)=2(8-x) | | 8x+9=5x+30 | | 3(x-2)-4(2x-3)=2(3x-1)-3(3x+1)+3 | | 3(2-3x)-2(5x-1)-3-2x=0 | | x-2(x-3)=5x+3(2x+2) | | 9x+24=5x+120 | | 5(3-x)-3(5-x)=0 | | -11=11(c-3) | | 99-5x=31x+15 | | 265-6x=39x+15 | | x^3+7x^2+200=0 | | 6(x-5)=-30 | | 15x=3(x-1)-4(1-x) | | -3=3(x+6) | | 149-5x=22x+23 | | 5x+13=-137-10x | | 7-5(x-2)=5-3(x+3) | | 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) |

Equations solver categories